Gambaran Pemahaman Mahasiswa S1 Pendidikan Biologi FKIP UKI Tentang Morfologi Tumbuhan dan Entomologi Melalui Biosketching - Adisti Ratnapuri (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this study was to describe the understanding of students' understanding of plant morphology and entomology specifically on the morphology and structure of insects in the Biology Education Study Program, FKIP Christian University of Indonesia. The research method is survey and content analysis. The research instrument was a non-test instrument. The data obtained are qualitative data in the form of resume biosketching and quantitative in the form of a questionnaire which is analyzed using percentage descriptive statistics. The results obtained were the first semester students with a score range of 65-80% in the understanding category, in the fifth semester students with a score of 90-100% in the very understanding category. This difference occurs because the fifth semester students have already received courses in plant morphology and entomology so that during the workshop they understand more about the morphology of the specimens drawn.